James Free papers - Free, James
Story files and scrapbooks of clippings (1937-1982) of Free's articles for various newspapers, particularly as Washington, D.C., correspondent for the Birmingham News covering the civil rights movement and the Cold War; articles for "National Whirligig," a newspaper column he coauthored with his wife, Ann Cottrell Free; notebooks (1965-1979) in which he recorded interviews and other information; and correspondence, notes, logbook, reports, and photographs documenting an expedition to the Caribbean in 1932 with L. Ron Hubbard to film exotic locales for motion pictures.
Journalist. Full name: James Stillman Free. Born 1908; died 1996.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Free, Ann Cottrell; Hubbard, L. Ron -- 1911-1986.; Birmingham news; African Americans -- Civil rights; American newspapers -- Alabama -- Birmingham; Civil rights -- United States; Civil rights movements -- United States; Cold War; Journalism -- Washington (D.C.); Motion pictures -- Caribbean Area; Journalists